REVOLUSI INDUSTRI 4.0 DAN TANTANGANNYA BAGI MANAJEMEN SUMBER DAYA MANUSIA PADA PERUSAHAAN INTERNASIONAL - Ari Budikusuma; Azry Triguna Nasution, Putri Safina, Dwi Wulandari, Rizki Rahmadani, Wilchan Robain (CV. ADIBA AISHA AMIRA, 2025)
Industrial Revolution 4.0 has brought fundamental changes in human resource management (HRM) in international companies. This research aims to analyze the impact of digital technology on HRM practices, identify the main challenges in implementing digital transformation, and formulate effective adaptation strategies. By using systematic literature review and content analysis methods, this research integrates various sources of scientific literature and case studies from global companies such as Microsoft, Unilever, DBS Bank, and Siemens. The research results show that the adoption of technologies such as Artificial Intelligence (AI), Big Data Analytics, and Cloud Computing improves operational efficiency, recruitment quality, and employee retention. However, challenges such as the digital competency gap, high turnover, and the need for more dynamic performance evaluation remain critical issues. Effective strategies include investing in reskilling and upskilling, implementing work flexibility, and strengthening employer branding. This study emphasizes the importance of a holistic approach that combines technology, strategy and the human touch to face change in the digital era.